Parents’ and carers’ experiences of transitions and aftercare following a child’s discharge from a pediatric intensive care unit to an inpatient ward setting: a qualitative systematic review protocol - Suleman, Zainab; Manning, Joseph C.; Evans, Catrin (Wolters Kluwer Health, 2016)
The primary objective of this review is to identify and describe parents’ and carers’ experiences of undergoing transitions and aftercare following a child’s discharge from pediatric intensive care Unit (PICU) to an inpatient ward environment for the treatment of an acute, life threatening critical illness or injury.